Aplikasi Informasi Gereja Katolik di Kota Semarang dengan Teknologi Web GIS (Information Technology and Telematics, 2015)
ABSTRACT Worship places are important and must be exist in every city, Church is one of the worship place used by Christians to assemble and pray. The lack of public knowledge about the church as well as its presence information (place) therefore it built an information technology that can help overcome these problems in order to the church's ministry to his people going well in step with public's knowledge about a church is increasing. Application Information for  Catholic Church is made  to provide information to the public or tourists who visit the city of Semarang on a church, where the user will know the spread of the Catholic Church in the city of Semarang, the position of the user, the path to the church and the church radius  input by the user. This application is displayed in the form of Web GIS-based thematic maps using Api Google Map. Keywoard: Chruch Information, Web GIS.